2019
DOI: 10.5213/inj.1938110.055
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Endoscopic Treatment Plus Maintenance Dimethyl Sulfoxide Therapy Prolongs Recurrence-Free Time in Patients With Hunner Type Interstitial Cystitis: A Pilot Study

Abstract: To evaluate whether hydrodistention with fulguration of Hunner lesions (HD/FUL) plus maintenance dimethyl sulfoxide (DMSO) therapy prolongs the recurrence-free time in patients with Hunner type interstitial cystitis (IC). Methods: The study enrolled patients with Hunner type IC who required repeat HD/FUL due to recurrence of IC symptoms after the first HD/FUL at our institution. All patients received a second HD/FUL plus maintenance DMSO therapy. The maintenance DMSO therapy was performed every 2 weeks for a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Of the 51 articles in MEDLINE, 7 focused on the treatment of HIC, including bladder instillation with dimethyl sulfoxide solution (DMSO), 68,69 triamcinolone acetonide, 70 tacrolimus, 71 bladder injection with human embryonic stem cell, 72 and the gold standard HIC treatment with fulguration of Hunner's lesion 73,74 . The other 18 studies focused on intravesical therapy of NHIC, including analysis and interpretation of published data showing cure of IC/BPS by uterosacral ligament repair, 75 clorpactin instillation, 76 intravesical hyaluronic acid (HA) instillation 77–79 or botulinum toxin‐A (BoNT‐A) injection 80–84 or combined treatment, 85 intravesical lidocaine instillation, 86,87 DMSO instillation, 88,89 intravesical injections of platelet‐rich plasma (PRP), 90 comparison of autonomic responses in different anesthesia types, 91 and stem cell treatment 92 .…”
Section: Current Treatment Modalities and Constructing Diagnostic And...mentioning
confidence: 99%
“…Of the 51 articles in MEDLINE, 7 focused on the treatment of HIC, including bladder instillation with dimethyl sulfoxide solution (DMSO), 68,69 triamcinolone acetonide, 70 tacrolimus, 71 bladder injection with human embryonic stem cell, 72 and the gold standard HIC treatment with fulguration of Hunner's lesion 73,74 . The other 18 studies focused on intravesical therapy of NHIC, including analysis and interpretation of published data showing cure of IC/BPS by uterosacral ligament repair, 75 clorpactin instillation, 76 intravesical hyaluronic acid (HA) instillation 77–79 or botulinum toxin‐A (BoNT‐A) injection 80–84 or combined treatment, 85 intravesical lidocaine instillation, 86,87 DMSO instillation, 88,89 intravesical injections of platelet‐rich plasma (PRP), 90 comparison of autonomic responses in different anesthesia types, 91 and stem cell treatment 92 .…”
Section: Current Treatment Modalities and Constructing Diagnostic And...mentioning
confidence: 99%
“…To prevent recurrence, the role of postoperative medication or intravesical treatment should be investigated. A recent pilot study reported that hydrodistension with fulguration of Hunner lesion plus maintenance DMSO therapy prolonged the recurrence-free time in patients with IC/BPS with Hunner lesion [20].…”
Section: Characteristics Of Recurrencementioning
confidence: 99%